Odpowiedź:
a) x = 2
b) x = 2
c) x = 2 lub x = - 2
Szczegółowe wyjaśnienie:
a) [tex](2^{x})^{3} = 64[/tex]
[tex](2^{x})^{3} = 4^{3}[/tex] / [tex]\sqrt[3]{}[/tex] ( wyciągam pierwiastek stopnia trzeciego )
[tex]2^{x} = 4[/tex]
[tex]2^{x} = 2^{2}[/tex]
x = 2
b) [tex](2^{3})^{x} = 64[/tex]
[tex](2^{x})^{3} = 4^{3}[/tex] / [tex]\sqrt[3]{}[/tex] ( wyciągam pierwiastek stopnia trzeciego )
[tex]2^{x} = 4[/tex]
[tex]2^{x} = 2^{2}[/tex]
x = 2
c) [tex](x^{2})^{3} = 64[/tex]
[tex](x^{6}) = 64[/tex]
[tex]x^{6} = 2^{6}[/tex] / [tex]\sqrt[6]{}[/tex] ( wyciągam pierwiastek stopnia szóstego )
x = 2 lub x = - 2